Studies on Development of Polymeric Materials Using Gamma Irradiation for Contact and Intraocular Lenses. (5th November 2009) - Chhabra, Pranshu; Gupta, Ruchi; Suri, Gunjan; Tyagi, Mukti; Seshadri, Geetha; Sabharwal, S.; Niyogi, U. K.; Khandal, R. K.
Abstract : For the development of materials for contact lenses and intraocular lenses, the selection criteria is based on the (i) capacity to absorb and retain water, (ii) hydrophilicity and hydrophobicity, (iii) refractive index and (iv) hardness besides the other essential properties. Various monomers are being studied to develop suitable materials for such applications. Selection of suitable monomers that can be converted into optical materials of desired characteristics is the most essential step. In the present paper, an attempt has been made to develop suitable optical polymers based on 2-hydroxy ethyl methacrylate (HEMA), N-vinyl pyrrolidone (NVP), methyl methacrylate (MMA), methacrylic acid (MAA), and styrene. Compositions were prepared in such a way that polymers of varying hydrophilicity or hydrophobicity could be obtained keeping HEMA as the base (main) monomer. For polymerization, gamma irradiation (Co-60 as a source) was used. The results of the study showed that: (i) an increase in NVP and MAA content brought in an increase in hydrophilicity of polymerized HEMA (pHEMA), while the addition of styrene and MMA decreased hydrophilicity of polymerized HEMA (pHEMA), (ii) polymers for contact lenses with water retention capacity as high as >50 wt.% and as low as <10 wt% with varying content of suitable comonomers can be designed, (iii) polymeric materials for contact lenses can be made by using radiation processing such as Co-60 and (iv) a dose of 40 kGy was found to be ideal for purpose.